Gamification and education: A pragmatic approach with two examples of implementation. Issue 1 (28th June 2021) - Willig, James H.; Croker, Jennifer; McCormick, Lisa; Nabavi, Meena; Walker, Jeremey; Wingo, Nancy P.; Roche, Cathy C.; Jones, Carolyn; Hartmann, Katherine E.; Redden, David
Abstract: Leveraging elements of game design and theories of human motivation, gamification provides a variety of techniques to engage learners in novel ways. Our Clinical and Translational Science Award created the software platform (Kaizen-Education©) to deliver gamified educational content in 2012. Here, we explore two novel use cases of this platform to provide practical insights for leveraging these methods in educational settings: (1) national training in rigor, reproducibility, and transparency and (2) attainment of learner competency (n = 7) as a gauge of curricular effectiveness across Master of Public Health degree tracks (n = 5). Data were captured in real time during player interaction with Kaizen-Education© to provide descriptive analyses of player engagement in both implementation examples. We then assessed item analysis to assess knowledge gain and competency attainment. We have just begun to leverage the potential for gamification to engage learners, enhance knowledge acquisition, and document completion of training, across various learning environments. We encourage a systematic approach to gamification applying insights from self-determination theory to learners and learning environments, a methodical approach to game design and rigorous analysis after implementation to generate evidence-based insights to maximize educational return for time invested.